Preparation and physical characterization of diamond thin films - Valera Palacios, Aníbal (2007)
This project involves the elaboration of diamond thin films from a plasmatic method, developed at the Laboratory of Optics and Semiconductors. The corresponding optical and electrical characterization of the elaborated materials.